Activated macrophages are the main inflammatory cell in COVID-19 interstitial pneumonia infiltrates. Is it possible to show their metabolic activity and thus the grade of inflammatory burden with 18F-Fluorocholine PET/CT?. (November 2020) - Savelli, G.; Bonacina, M.; Rizzo, A.; Zaniboni, A.
Abstract: The recent outbreak of Covid-19 has represented a major challenge for the countries affected by the disease, not only in terms of loss of human life, economic downturn, and constraint on individual freedom, but also for the great pressure on the national health systems and hospitals. The 380 kDa virus has been a perfect storm, especially for those national health systems used to working with limited resources and high intensity rhythms, such as Italy. For the first time in the new century, a virtually unknown fast-spreading disease has caused a public health emergency thus forcing most countries to deal with an insurmountable logistic gap. Hence, every branch of Medicine, even though not directly involved in the treatment, has been called upon to provide its contribution to resolve the crisis. It is now becoming more apparent that Covid-19 is not solely a lung disease, but a complex systemic disease involving several organs and systems. This is due to an abnormal inflammatory response which eventually leads to multisystemic coagulopathy which mainly, but not uniquely, targets the lungs. Although the pathophysiology of this syndrome is still not fully understood, macrophages and their immune complex system seem to play a key role. It is not yet clear why some patients develop the violent immune response which results in pneumonitis while others do not. There are clues indicating that the systemic hyper-inflammation defined as macrophage activation syndrome (MAS), or cytokine storm, requires an increase in choline consumption to synthesize phosphatidylcholine and stimulate phagocytosis, organelle biogenesis, secretory functions, and endocytosis. 18 F-Fluorocholine is a synthetic analog of the naturally occurring choline normally used for PET/CT imaging of prostate cancer patients. 18 F-Fluorocholine could image and quantify the macrophage activity in pulmonary interstitial infiltrates of Covid-19 pneumonia. If the hypothesis is confirmed experimentally, 18 F-Fluorocholine PET/CT could be used to in vivo image and quantify the degree of lung inflammation and potentially stratify the gravity of this disease.